Analysis of Improvement of Employee Work Posture Using OWAS Method (case study at PT. XYZ) - M. Bachmid, Zainal Abidin; Andesta, Deny (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
PT. XYZ is a service company in the field of construction and fabrication. This study aims to determine the results of work postures in the company and determine the level of risk for operators based on the nordic Body Map (NBM) and provide suggestions for improving work posture to the operator. Ovako Work Posture Analysis System(OWAS) is a method for evaluating and analyzing the work attitude of observed operators, including body movements of the back, shoulders, arms, and legs, including thighs, knees, and ankles. This method is fast in identifying work attitudes that have the potential to cause work accidents. Work accidents that are of concern to this method are the musculoskeletal system. It is known that there are 4 work postures from the company PT XYZ, out of these four postures need improvement as soon as possible. It is recommended to pay more attention to the health and safety of operators, especially during disturbancesMusculoskeletal disorders which are caused by unsuitable work environment conditions and workload which can result in decreased work productivity